Factors Predicting Quality of Life among Elderly People at Geriatric Homes in Baghdad City - Khamis, Shahad H.; Mohammed, Zahid J. (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): This study aimed to assess quality of life among elderly in geriatric homes and its influencing factors. Methods: A descriptive cross-sectional study conducted in a geriatric home in Baghdad for the period from November 1st, 2022 to March 1st, 2023, on a sample of (139) elderly people. A validated WHOQOL-BREF questionnaire was used with a total number of 28 items for quality-of-life assessment. Data were collected using interviews and analyzed by applying descriptive and inferential statistical analysis. Results: The results indicate that the average age of the participants was 72.15 (± 2.39) years, more than half of the participants were males (58.3%), the monthly income was less than 300 thousand Iraqi dinars (45.3%), more than half of them have sons (59.7%). The results showed that (55.4%) of the elderly expressed a low quality of life. The study indicated that participants age, sex, marital status, monthly income, educational level, who have sons, length of stay in a geriatric home, and associated chronic diseases are all factors that predict quality of life among the elderly (p<0.05). Conclusion: The level of quality of life among the elderly was poor due to many influential socio-demographic characteristics such as age, gender, marital status, monthly income, education, occupation, length of stay in the geriatric home, and comorbid chronic diseases that are factors that predict the quality of life among the elderly. Recommendations: The study boosts an understanding on how elderly sociodemographic characteristics predicts their quality of life in geriatric homes. More research is required to exploring geriatric demands and the standard of services offered.